An Analysis of Rodent Reservoirs of Plague During the Second Pandemic: Shifting Focus Towards a Multi-host and Multi-mechanism Model of Plague Maintenance and Reintroduction in the Past - Tapson, Madeline (My University, 2020)
The second pandemic persisted for 500 years throughout Europe and some regions of Africa and Asia and far surpasses the first and third pandemics in terms of temporal and spatial breadth. It is still unclear what mechanisms facilitated the long-term maintenance and continued disease reintroductions experienced during the second pandemic. Many researchers believe it was the spread of plague infected Rattus spp. via trade routes, while others are beginning to support a model that reflects modern plague ecology such that plague was maintained in local rodent reservoirs in the Mediterranean region or Europe following its 14th century introduction. This study accumulated a list of rodent species known to host plague and analyzed host characteristics to determine what traits allow rodents to function as successful reservoir species. In addition, this study analyzed the ancient DNA within rodent remains in search of Yersinia pestis to add to the history of the pathogen. The results of this study demonstrate that there are 45 non-Rattus rodent species known to host plague within a modern context. Although ancient Y. pestis DNA was not identified from zooarchaeological remains within this study, it is clear that rodent reservoirs were key players in past plague pandemics. When viewed through the lens of a single model (i.e. trade routes or human-ectoparasites), several questions about past plague maintenance remain unanswered. This study shows that a more complex composite model is best fit to describe the 500-year reign of the second pandemic and the quiescent periods that extended between the cyclical disease reintroductions. This study presents the first comprehensive, interactive, and publicly available online database of rodent reservoirs to aid in future research and emphasizes the need to investigate a multi-mechanism model of plague maintenance and reintroduction in the past. With this research we facilitated a starting point for future studies, expanded the current knowledge on rodent reservoirs of plague, and contributed a valuable discussion to the field of plague studies on regions that have thus far gone underserved in plague studies, such as the Mediterranean littoral.
Keywords: Plague; second pandemic; Mediterranean littoral; rodent reservoirs